Effects of postmilling time and temperature on the breadmaking quality and lipids of whole wheat flour - Stoerzinger, Karolyn M. (Kansas State University, 2009)
This work investigated the relationship between flour age (days post-milling), storage condition (temperature), and the bread baking quality of whole wheat flour. A laboratory scale milling method was designed to mimic the particle size distribution of commercially milled whole wheat flours and the 100 g ‘pup’ loaf baking method was adapted for use with whole wheat doughs. Laboratory milled whole wheat flour (Karl 92) was subjected to a 21 day storage study at two storage temperatures (72 & -15 F) with quality (baking) and chemical (lipids) analyses conducted every three days. Parameters for quality analysis included: loaf weight, volume & specific volume, as well as slice area, cell number, wall thickness, cell diameter, elongation, and non-uniformity. Three lipid classes (glycolipids, phospholipids, and neutral lipids) were extracted and analyzed by TLC with quantification by computerized analysis of spot size and density. Results were analyzed by ANOVA. Analysis of the loaf quality data revealed no trends in volume or specific volume as a function of storage time or temperature, although values for some specific days were significantly different. Likewise, analysis of crumb characteristics revealed no consistent trends for either time or storage temperature. Again, values for some, but not all, parameters (area, brightness, wall thickness, cell diameter, and non-uniformity) were significantly different for specific days of the study. Analysis of lipids revealed no consistent trends for either time or storage temperature. However, values for some lipid classes (total glycolipids, free phospholipids, and total phospholipids) were significantly different for storage temperature, and values for total neutral lipids were significantly different for specific days of the study. Suggested future research opportunities include: using new crop wheat, increasing storage duration, performing WW flour lipid exchange studies, and using lipid profiling to identify and more closely track changes in individual lipid species.
Keywords: bread; lipid; storage; wheat; baking; flour; Agriculture, Food Science and Technology (0359)